Treatment approach in patients with hyperbilirubinemia secondary to liver metastases in gastrointestinal malignancies: a case series and review of literature - Quidde, J (2016)
BACKGROUND: Treatment of patients with severe liver dysfunction including hyperbilirubinemia secondary to liver metastases of gastrointestinal (GI) cancer is challenging. Regimen of oxaliplatin and fluoropyrimidine (FP)/folinic acid (FA) ± a monoclonal antibody (moAb), represents a feasible option considering the pharmacokinetics. Clinical data on the respective dosage and tolerability are limited and no recommendations are available. METHODS: Consecutive patients with severe hyperbilirubinemia [>2 × upper limit of the normal range (ULN) and >2.4 mg/dl] due to liver metastases of GI cancer without options for drainage receiving oxaliplatin, FP/FA ± moAb were analyzed. To collect further data a review of the literature was performed. RESULTS: A total of 12 patients were identified between 2011 and 2015. At treatment start, median bilirubin level was 6.1 mg/dl (>5 × ULN, range 2.7-13.6). The majority of patients (n = 11) received dose-reduced regimen with oxaliplatin (60-76%) and FP/FA (0-77%), rapidly escalating to full dose regimen. During treatment, bilirubin levels dropped more than 50% within 8 weeks or normalized within 12 weeks in 6 patients (responders). Median overall survival was 5.75 months (range 1.0-16.0 months) but was significantly prolonged in responders compared to nonresponders [9.7 and 3.0 months, p = 0.026 (two-sided test); 95% confidence interval (CI): 1.10-10.22]. In addition, case reports or series comprising a further 26 patients could be identified. Based on the obtained data a treatment algorithm was developed. CONCLUSION: Treatment with oxaliplatin, FP/FA ± moAb is feasible and may derive relevant benefits in patients with severe liver dysfunction caused by GI cancer liver metastases without further options of drainage.